(untitled) (International Journal of Engineering and Computer Science, 2017)
This project is very useful for this modern world. The best way of controlling the Traffic light system through IOT. This project is a prototype with two traffic light system. There are many platforms which provides a bridge between the user and the device. Here this device use the best and simple IOT platform “Thingspeak”. In this generation, there are many way of controlling the traffic light system like traffic density calculator. It is waste of time standing idle even at the night time when there is no heavy traffic. This project will be useful for the Traffic Authority to control the particular signals via online from anywhere. The main component is Raspberry Pi 3 and Webpage prototype. This device is designed in such a way to avoid accidental switches. It is possible to control more number of traffic lights with upgradation in python and HTML coding